Precision measurements of cosmic ray air showers with the SKA - Huege, T.; Bray, J.; Buitink, S.; Dallier, R.; Ekers, Ronald; Falcke, H.; James, C.; Martin, L.; Revenu, B.; Scholten, O.; Schröder, F. (SPIE - Internatioal Society for Optocal Engineering, 2014)
Supplemented with suitable buffering techniques, the low-frequency part of the SKA can be used as an ultra-precise detector for cosmic-ray air showers at very high energies. This would enable a wealth of scientific applications: The physics of the transition from Galactic to extragalactic cosmic rays could be probed with very high precision mass measurements, hadronic interactions could be studied up to energies well beyond the reach of man-made particle accelerators, air shower tomography could be performed with very high spatial resolution exploiting the large instantaneous bandwith and very uniform instantaneous u-v coverage of SKA1-LOW, and the physics of thunderstorms and possible connections between cosmic rays and lightning initiation could be studied in unprecedented levels of detail. In this article, we describe the potential of the SKA as an air shower radio detector from the perspective of existing radio detection efforts and discuss the associated technical requirements.